PPM PELATIHAN GAME EDUKATIF SCRATCH GUNA MEMBANGUN KREATIVITAS DAN LITERASI DIGITAL - Muhammad Harist Murdani; Mamik Usniyah Sari; Fitriya Gemala Dewi (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
This Community Engagement Program was conducted at Wijaya Putra Senior High School, Surabaya, which faces challenges of low digital literacy and limited platforms for developing students’ creativity in interactive technology. The program aims to enhance logical and creative thinking skills as well as the utilization of digital technology through training in the development of Scratch-based educational games. The implementation method consists of several stages: socialization, intensive practice-based training (learning by doing), mentoring for final projects, evaluation of student works, and the establishment of the “Scratch Creative Class” community as a sustainability strategy. The expected outcomes include improved student skills in producing interactive digital media, the establishment of a coding community within the school, the creation of student project portfolios, and the dissemination of program results through CSR-PKM proceedings and mass media. This program is expected to strengthen students’ digital literacy, foster creativity, and build a technology-based educational ecosystem within secondary schools.